Mandibular advancement devices, irrespective of amount of movement, are effective in treating young patients with obstructive sleep apnea - Wei Min Natalie Tan; Kok Weng Lye; Seyed Ehsan Saffari; Choy Yoke Poon (Sleep Science and Practice)
Abstract Introduction Mandibular advancement devices (MADs) increase the airway by providing a stable anterior position of the mandible, advancing the tongue and soft palate and potentially changing the genioglossus muscle activity. As such they are an accepted non-surgical treatment option for obstructive sleep apnea (OSA). The study aimed to investigate whether the amount of mandibular advancement impacts treatment outcomes of OSA. Secondary aims included identifying variables correlated with treatment response and assessing changes in polysomnography (PSG) parameters based on advancement. Methods This retrospective study included patients aged ≥ 18 years diagnosed with OSA and treated with MADs. Data were collected from clinical notes, pre- and post-treatment PSG sleep studies. Amount of advancement was determined by the final titrated advancement achieved. Patients were grouped according to whether the final amount of advancement was ≤ 8 mm or > 8 mm. Treatment responses were classified as complete (symptom resolution and RDI < 5/h), partial (symptom improvement and ≥ 50% reduction of RDI but RDI ≥ 5/h) and no response (< 50% reduction in RDI and RDI remaining ≥ 5/h). Treatment responses and changes in PSG parameters (T90, LSAT and RDI) were then compared between the two groups of patients. Results The study included 49 patients (42 males, 7 females) with mild (n = 9), moderate (n = 28), and severe (n = 12) OSA. No statistically significant difference was found for OSA severity between male and females. Complete response rate was 11.1% for ≤ 8 mm advancement and 19.4% for > 8 mm advancement, but this difference was not statistically significant. Similarly, changes in RDI, LSAT and T90 were not statistically significant between the two groups. There was statistically significant difference in treatment response between age groups, with younger patients (≤ 50 years) showing better response. Conclusion Effectiveness of MADs in the treatment of OSA does not depend on the final titrated advancement achieved. However, younger patients benefit more from MADs, highlighting age as a critical parameter in treatment responses. Clinical implications There is strong evidence to support the use of MADs as a functional second line treatment option to CPAP, and thus understanding the factors that contribute to positive treatment of OSA is important.